PEMBERDAYAAN REMAJA DALAM MENINGKATKAN PEMAHAMAN PERGAULAN BEBAS MELALUI DIALOG EDUKATIF DAN KEGIATAN KREATIF DAUR ULANG - Yulia Eka Yanti; As Syafaatussalamah; Dian Novita Sari; Dina Maftuhatul Rizky; Maulidhatul Hasanah; Tety Nur Cholifah; Hendra Rustantono; Bella Cornelia Tjiptady (FIP UNIRA MALANG, 2026)
ABSTRACT This Community Service Program (PKM) was carried out in response to the increasing vulnerability of adolescents to risky behaviors associated with free association, which is often triggered by limited parental supervision and a lack of understanding about its consequences. The program aimed to enhance adolescents’ awareness of the dangers of free association while providing them with positive alternative activities that support healthier behavioral development. The implementation methods included educational dialogues, interactive discussions, field observations, and a practical session on creating keychains from recycled bottle caps. Throughout the program, participants demonstrated noticeable improvements, reflected in their growing confidence to ask questions, engage in discussions, and share personal experiences. In addition to gaining new insights into the impacts of risky social interactions, the adolescents were able to develop creativity through the craft-making activity, which offered them productive options for spending their free time. Overall, this PKM activity contributed positively to strengthening awareness, preventive attitudes, and responsible social behavior among adolescents, fostering a healthier and more mindful approach to peer interactions.